Relevance of adaptive protection scheme using phasor measurement unit in Indian power grid. (2019) - Kumar, Deepa S.; Savier, J.S.
The configuration of the power system is constantly changing due to renewable integration, changing loads, network switching operations or faults. The relays settings based on pre-determined static system conditions that are in general maximum or minimum, may not suffice, leading to inaccurate relay operation for a dynamic power system. Malfunction of conventional protection system has been one of the main causes of cascading catastrophes in power grid. Selection of suitable relay characteristics that will be an appropriate compromise for all loading conditions and contingencies is a matter of concern. The relevance of adaptive relay settings in wide area monitoring, protection, and control (WAMPAC) using synchrophasor is brought out in this paper. The significance of new wide area adaptive protection system (WAAPS) in improving the reliability and safety of power transmission through Indian grid, with a high level of operational uncertainties, is analysed and an architecture is suggested.